Pengembangan Model Pencegahan Kekerasan pada Remaja: Systematic Literature Review - Sally Pratama Nuryani; Badriati B Porogoi; Ririn Sriharyanti; Luzi Febriani; Andi Julia Rifiana; Lisa Trina Arlym (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Violence against youth is a public health problem of growing global concern. Comprehensive educational interventions are needed to improve adolescents' social and emotional resilience. This study aims to identify an effective educational model that integrates elements of self-awareness, assertiveness, digital and emotional literacy, a supportive environment, and peer facilitation. The research method used was a systematic literature review with a search strategy in five major databases (PubMed, EBSCO, ProQuest, SpringerLink, and ScienceDirect) over the past five years. A total of seven articles were selected based on PICOS selection criteria and critical quality assessment. The review results indicate that a community-based educational approach involving active adolescent participation and ongoing character education is effective in preventing violence. Therefore, developing a contextual and holistic educational model may be an appropriate strategy in preventing violence against youth.